Hilfer-Hadamard Nonlocal Integro-Multipoint Fractional Boundary Value Problems - Chanon Promsakon; Sotiris K. Ntouyas; Jessada Tariboon (Journal of Function Spaces)
This paper is concerned with the existence and uniqueness of solutions for a new class of boundary value problems, consisting by Hilfer-Hadamard fractional differential equations, supplemented with nonlocal integro-multipoint boundary conditions. The existence of a unique solution is obtained via Banach contraction mapping principle, while the existence results are established by applying Schaefer and Krasnoselskii fixed point theorems as well as Leray-Schauder nonlinear alternative. Examples illustrating the main results are also constructed.